2018
DOI: 10.3889/oamjms.2018.388
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 25-Hydroxyvitamin D and Lipid Profile among Children with Beta Thalassemia Major

Abstract: BACKGROUND:Beta thalassemia major is associated with lipid profile abnormalities, presented as a lower level of total cholesterol (TC), low-density lipoproteins (LDL), high-density lipoprotein (HDL), and higher triglyceride level; increasing risk for cardiovascular complications. The previous studies indicated that Vitamin D give a positive impact on the lipid profile in healthy children population. However, its role needs to be determined in a high-risk group of children with beta-thalassemia major.AIM:To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…These results are consistent with previous studies. [ 32 , 33 ] These results indicate that a deterioration of both lipid metabolism and calcium homeostasis may occur due to 25(OH)D deficiency in patients with calcaneal spurs.…”
Section: Discussionmentioning
confidence: 88%
“…These results are consistent with previous studies. [ 32 , 33 ] These results indicate that a deterioration of both lipid metabolism and calcium homeostasis may occur due to 25(OH)D deficiency in patients with calcaneal spurs.…”
Section: Discussionmentioning
confidence: 88%
“…Acting through various selenoproteins, selenium plays a vital role in thyroid hormone metabolism, DNA synthesis, and protection against free-radical damage. Serum selenium, as well as plasma activity of glutathione peroxidase, were commonly found to be lower in adult subjects with Thal compared with healthy controls, regardless of chelator type 48–50. Nasr et al51 also reported a negative relationship between selenium and serum ferritin in 64 transfusion-dependent Egyptian children with Thal.…”
Section: Resultsmentioning
confidence: 99%
“…Serum selenium, as well as plasma activity of glutathione peroxidase, were commonly found to be lower in adult subjects with Thal compared with healthy controls, regardless of chelator type. [48][49][50] Nasr et al 51 also reported a negative relationship between selenium and serum ferritin in 64 transfusiondependent Egyptian children with Thal.…”
Section: Seleniummentioning
confidence: 95%
See 1 more Smart Citation
“…The fact that transfusion-dependent thalassemia was more prone to bacterial infection supports the alteration of immune function in this genetic disease [ 64 ]. The correlation of vitamin D deficiency in β-thalassemia has been known to alter the cardiovascular system [ 62 , 65 ], endocrines [ 66 ] and the bone [ 15 , 67 ]. A study involving all types of thalassemia, including β-thalassemia, supplementation of 50,000 IU of ergocalciferol (vitamin D 2 ) could increase the 25-OHD level; however, the effect of this supplementation on the immune system was not investigated [ 61 ].…”
Section: Resultsmentioning
confidence: 99%